Factors of consolidation as the terms of sustainable development of society in Kazakhstan (Journal of Philosophy Culture and Political Science, 2019)
In given article the main factors of consolidation of Kazakhstan society on the way of transforming of Kazakhstan to sustainabledevelopment are revealed. Consolidation process of Kazakhstani society is considered by taking account economic-geographical, socialpoliticalfeatures, ethnical and confessional structure of society and also historical experience of other countries. Authors conclude thatsocial-economic, political, ideological, ethnical and intellectual-cultural factors of unity of people only in the complex are able toprovide successful transforming of Kazakhstan society to sustainable development.